High adsorption of methylene blue from aqueous solutions using leaf-shaped ZIF-8. Issue 14 (14th November 2021) - Alinejad, Abdolazim; Sadeghi, Shahram; Ghaderpoori, Mansour; Sahebi, Soleyman; Ghaderpoury, Afshin; Mohammadi, Ali Akbar; Saghi, Mohammad Hossien; Gholampour, Yousef; Khani Jeihooni, Ali
ABSTRACT: Dyes are one of the most important environmental pollutants that have a significant impact on the environment, especially water resources. Dyes are toxic compounds that have severe effects on the environment. Methylene blue dye (MBD) causes problems like nausea, profuse sweating, vomiting, mental confusion, and methemoglobinemia. In this study, ZIF-8 with leaf-shaped morphology was used for MBD adsorption. All experiments were performed in batch conditions. The Leaf-shaped ZIF-8 is obtained at the molar ratio of 2-methylimidazole/Zn = 8. The prepared leaf-shaped ZIF-8 was white powder. The as-synthesis adsorbent is in the form of the leaves of a tree. The thickness of Leaf-shaped ZIF-8 is about 6–98 nm. Alkaline conditions were much more favourable than acidic to MBD adsorption. By increasing the dosage of Leaf-shaped ZIF-8, MBD adsorption increased until reaching an equilibrium dose at 0.5 g/L. the kinetic model of pseudo-first-order and the isotherm model of Langmuir have the highest coefficient of determination (R-square). Based on the Langmuir model, the maximum capacity of MBD adsorption on the Leaf-shaped ZIF-8 was 205 mg/g. In this study, the RL was less than one which indicates MBD adsorption is favourable. Also, based on the Freundlich model, 1/n was 0.26, favourable adsorption condition was favourable.